Perinatal complications in women with gestational diabetes mellitus - Hafija Akter,; Tamima Akter,; Ummay Kulsum,; Munira Parveen, (International Journal of Research in Medical Sciences, 2023)
Background: Gestational diabetes mellitus (GDM) is glucose intolerance during pregnancy, with or without remission after pregnancy. It poses risks to the mother and baby, including future maternal diabetes and up to 42.9% perinatal mortality. Proper diagnosis and management can improve outcomes. This study analyzes perinatal complications in women with GDM. Methods: This cross-sectional study was conducted at the department of obstetrics and gynecology in Uttara Adhunik medical college and hospital, Dhaka, Bangladesh for 1 year; January 2020- December 2020. A total of 50 subjects who were admitted in the hospital and diagnosed with GDM were included in this study. Informed written consent was taken from the study subjects. A pretested interviewer-administered questionnaire was used to obtain information related to the sociodemogic status, level of education, types of profession, and medical history. A descriptive analysis was done. Data processing and analysis were done by using SPSS version 17. Results: Most subjects (35, 70%) belonged to the <25 years age group followed by (15, 30%) ≥25 years age group. Among the respondents, most (30, 60%) reside in rural areas of Bangladesh followed by (20, 40%) in urban areas. Regarding socioeconomic status, most of the subjects (25, 50%) came from a low socioeconomic condition, followed by (20, 40%) from middle socioeconomic status, and only 5 (10%) patients came from a high socioeconomic condition. Among all the diagnosed GDM cases, the majority of perinatal complications was macrosomia (14%), followed by neonatal respiratory distress (12%), newborn polycythemia (6%), preterm birth (4%), stillbirth (2%) and congenital malformation (2%). Regarding maternal and placental complications, gestational hypertension was the most common (14, 28%), followed by vaginal candidiasis (12, 24%), premature rupture of membrane (9, 18%), and abruptio placenta (6, 12%). Conclusions: This study concluded that the most common perinatal complication was macrosomia, followed by neonatal respiratory distress, newborn polycythemia, preterm birth, stillbirth, and congenital malformation.